Null effect of antidepressants on the astrocytes-mediated proliferation of hippocampal progenitor cells in vitro - Kaang Bong-Kiun; Son Hyeon; Lee Sung; Ko Hyoung-Gon (SAGE Publishing, 2007)
Abstract Background It is well known that antidepressants increase neurogenesis in the dentate gyrus of the hippocampus. The increase of neurogenesis might contribute to the behavioral effects of antidepressants. However, the mechanism by which antidepressants increase hippocampal neurogenesis is largely unknown. It has been recently reported that astroglia induce the neurogenesis of the hippocampal neural progenitor cells (NPCs). Therefore, we hypothesized that antidepressants may act on astrocytes, and this in turn induces neurogenesis of NPCs. Results To examine this hypothesis, we used two co-culture systems, i.e., a contact-independent Banker culture and a contact-dependent overlay co-culture. In both of these systems, in comparison with naïve astrocytes, antidepressant-treated astrocytes did not further increase the proliferation of NPCs. Conclusion These results suggest that astrocytes increase the proliferation of hippocampal NPCs, however, this may not be directly involved in the antidepressant-induced proliferation of NPCs.